Klebsiella pneumoniae: an increasing threat to public health - Clement Yaw Effah; Tongwen Sun; Shaohua Liu; Yongjun Wu (BMC, 2020)
Abstract Objectives This review fills the paucity of information on K. pneumoniae as a nosocomial pathogen by providing pooled data on epidemiological risk factors, resistant trends and profiles and resistant and virulent genes of this organism in Asia. Methods Exhaustive search was conducted using PubMed, Web of Science, and Google scholar for most studies addressing the prevalence, risk factors, drug resistant-mediated genes and/or virulent factors of K. pneumoniae in Asia. Data extracted for meta-analysis were analyzed using comprehensive meta-analysis version 3. Trends data for the isolation rate and resistance rates were entered into Excel spread sheet and the results were presented in graphs. Results The prevalence rate of drug resistance in K. pneumoniae were; amikacin (40.8%) [95% CI 31.9-50.4], aztreonam (73.3%) [95% CI 59.9-83.4], ceftazidime (75.7%) [95% CI 65.4-83.6], ciprofloxacin (59.8%) [95% CI 48.6-70.1], colistin (2.9%) [95% CI 1.8-4.4], cefotaxime (79.2%) [95% CI 68.0-87.2], cefepime (72.6) [95% CI 57.7-83.8] and imipenem (65.6%) [95% CI 30.8-89.0]. TEM (39.5%) [95% CI 15.4-70.1], SHV-11 (41.8%) [95% CI 16.2-72.6] and KPC-2 (14.6%) [95% CI 6.0-31.4] were some of the resistance mediated genes observed in this study. The most virulent factors utilized by K. pneumoniae are; hypermucoviscous phenotype and mucoviscosity-related genes, genes for biosynthesis of lipopolysaccharide, iron uptake and transport genes and finally, adhesive genes. Conclusion It can be concluded that, antimicrobial resistant in K. pneumoniae is a clear and present danger in Asia which needs strong surveillance to curb this menace. It is very important for public healthcare departments to monitor and report changes in antimicrobial-resistant isolates.